Influence of surface roughness on the bandwidth of optical multimode waveguides analyzed by modal noise theory - Stübbe, Oliver; Bierhoff, Thomas; Schrage, Juergen; Mrozynski, Gerd (Wave Optics and Photonic Devices for Optical Information Processing II)
Modal noise is an undesired modulation of the guided light intensity in a multimode waveguide. Applying the frequency correlation function the frequency dependence of this noise as well as the bandwidth of a multimode waveguide can be estimated. In this paper the existing model of the frequency correlation function for a waveguide with smoothed dielectric interfaces is enhanced to analyze the influence of surface roughness on the achievable bandwidth. This surface roughness is caused by the manufacturing process of the waveguides.